Hypertension Prevention And Control Strategy In Pre-Elderly At Danau Sembuluh Health Center UPTD In 2024 - Ramasih, Ramasih; Mustopa, Mustopa; Ruspandian Noor (Sean Institute, 2024)
Pre-elderly hypertension at the Danau Sembuluh Health Center UPTD is relatively high, even though the Seruyan Regency Government has created a health service program for hypertension sufferers according to the standards stated in the Seruyan Regent Regulation Number 2 of 2023 and the Regulation of the Minister of Health of the Republic of Indonesia Number 6 of 2024 concerning minimum technical standards for health services. This study aims to evaluate the prevention and control strategy for hypertension in pre-elderly at the Danau Sembuluh Health Center UPTD. The method used is a qualitative approach with a case study design because it aims to gain a deep and comprehensive understanding of a specific case, namely the hypertension prevention program at the Danau Sembuluh Health Center. Data were collected through in-depth interviews with several informants, field observations, and analysis of relevant documents. Data analysis was carried out using coding, categorization, and thematic analysis techniques. The results of this study identify the great potential of the hypertension prevention and control program in Seruyan Danau Sembuluh Regency. However, to achieve optimal results, efforts are needed to improve the quality of health workers, allocate a more adequate budget, and improve coordination between various parties. Thus, this program can be more effective in reducing the number of hypertension sufferers and improving public health.